The Analysis Role of Social Skills and Principal’s Performance on School’s Culture of Private Islamic School - Fitria Khasanah; Muhammad Zainuddin; Akhmad Ramli; Primadi Candra Susanto; Revi Sesario (Journal on Education, 2023)
This study's objective is to determine whether school culture is influenced by the social abilities of the principal. Does the principal's performance have any impact on the culture of the school. And does the success of school principals have any bearing on the culture of the schools. This study employs quantitative methodologies, with questionnaires and non-experimental designs serving as data gathering tools. The sample for the study consisted of 72 people who worked as teachers or staff. The study's findings demonstrate that principals' social abilities have a big impact on the culture of schools. School culture is positively impacted by the performance of the principals. Each school principal has a varying level of influence over school culture, but all of them positively affect it with their performance and social abilities